(untitled) («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
Today, over time, one can observe the return of individual words from the layer of obsolete words to use, and even the use of some of them is becoming popular. This situation, associated with social, political, personal and religious factors, requires the study of changes in the semantics of obsolete words in the language. This article is about a layer of obsolete words and some words that are now back in use.